Selecting Line of Business (LOB) Development Priority Using Analytical Hierarchy Process - Zico Andrea Aripratama; Sylviana Maya Damayanti (Publikasi Indonesia, 2026)
PT Asuransi Kredit Indonesia (Askrindo), a state-owned insurance company and a member of the Indonesia Financial Group (IFG) holding, is currently facing a significant strategic agenda. Prior to this initiative, Askrindo’s parent company experienced a declining performance trend, as reflected by a 20% year-on-year decrease in gross written premiums (GWP) in 2025, while its combined ratio increased to 112% during the same period. This condition differed from the overall industry performance, as data from the Financial Services Authority (Otoritas Jasa Keuangan or OJK) indicated that the general insurance industry recorded 3% premium growth in 2025 while maintaining a combined ratio of approximately 71%. Askrindo’s business portfolio remained highly concentrated in the financial lines of business (LOB), which accounted for 88% of the company’s total portfolio in 2025. Therefore, portfolio diversification through the development of non-financial lines of business has become one of the company’s key strategic priorities. Askrindo needs to optimize its existing LOB portfolio to generate added value and maintain competitive advantage amid the consolidation of state-owned insurance companies.Based on these conditions, this study aimed to evaluate Askrindo’s financial performance compared with industry competitors and other companies within the IFG holding. Furthermore, this study sought to determine priority LOBs for further development using the Analytic Hierarchy Process (AHP). At the LOB level, the AHP framework identified Miscellaneous (microinsurance products), Suretyship, and Property as the priority business lines for further development by Askrindo.